DEVELOPMENT OF STRATEGY ON CITRONELLA PRODUCTS TO OPTIMIZE AGRIBUSINESS POTENTIAL IN RURAL AREAS (STUDY IN CIPATAT VILLAGE KEC. CILENGKRANG WEST JAVA) - Bestari, Dinda Kayani Putri; Nurwita, Ni Putu; Rachmawati, Mariana; Lisdayanti, Annisa; Dalimun, Gallang Perdhana; Munawar, Fansuri (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Rural Agribusiness Empowerment Strategy arises from the problem of inequality in regional development between cities as centers of activity and economic growth with producing areas as centers of less developed agricultural activities. . This condition occurs in Cipatat Village, Cilengkrang District, Ciporeal Village, West Java. This village, is an area that has good potential to be used as land or land for Agribusiness, but this potential is not utilized optimally by the community around the village, where Cipatat Village has a mainstay product of Citronella fragrant. This study aims to find the effect of product quality and distribution of Cipatat Village's fragrant lemongrass products on purchasing decisions. The method used in this study is descriptive verification with data analysis techniques using multiple regression analysis. The number of respondents in this study were 36 respondents where the respondents were consumers of Cipatat Village Citronella Fragrant. From the results of the study, it was found that there was an influence between product quality and distribution of Cipatat Village's Citronella fragrant products on purchasing decisions with an influence value of 36.8%.